ANALISIS METODE JARI MAGIC (JARIMATIKA) DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN DAN MOTIVASI BELAJAR SISWA - Mutaqin, Ejen Jenal; Muslihah, Neni Nadiroti; Tilawati, Lisna (IPI Press, 2021)
This research is motivated because some students still find it difficult to count, especially in multiplication, this has an impact on learning motivation, therefore researchers are interested in this study which aims to improve numeracy skills and student motivation in learning to count through learning with Jarimatika. This study involved 6 students consisting of 3 participants from class III and 3 participants from class IV. This research method uses a qualitative approach with descriptive methods. This data was obtained by means of tests, motivation questionnaires, and interviews. The data analysis technique in this study uses the process of data collection, data reduction, data display, and conclusion / verification. As for the results of the research using Jarimatika in numeracy skills for class III, the learning activities are practicing Jarimatika, printing fingers and arranging puzzles with an average score of 8.77 and for grade IV the learning activities are matching pictures, pasting cards and the circumference of Nusantara with the average score. 8.66. Meanwhile, for the result of learning motivation for class III gets an interpretation value of 3.22 which is classified into the